PREVALENCE OF EXFOLIATIVE TOXIN GENES AMONG CLINICAL ISOLATES OF STAPHYLOCOCCUS AUREUS IN IRAQ - Yassin, H. Y.; Melconian, A. K.; Mahmood, S. S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The aim of this study is to determine the prevalence of eta, etb and etd genes among clinical isolates of S. aureus. 91 isolates of the bacterium were isolated from different clinical sites during the period from 2019 to 2020 from Baghdad hospitals, all the isolates were diagnosed by different biochemical tests and molecular method (PCR) using nuc gene. the PCR technique was used to detect eta, etb and etd genes among the isolates, the results showed that 91(100%) of the isolates were have nuc gene. while, 83 ( 91.2%) of the isolates at least carrying one of the ET genes; 20 (22%) , 0 (0%) and 63 (69.2%) of the 91 isolates expressed eta, etb and etd genes, respectively. While, 8 (8.8%) of isolates were lacking of these genes. In addition, 14 (15.4%) of isolates were carrying both eta and etd genes. Although the etd gene was found in all sample types, but eta gene was found only in wound, ear, throat and nose while, etb gene was not found in all types of clinical samples.